Experimentation in executable enterprise architecture models (2011)
Enterprise Architecture (EA) is a multidimensional model-based approach which enables analysis and decision-making in organizations. Currently, most EA approaches produce models that are inherently static: they focus on structural qualities of the organizations and represent their state in only one specic point in time. Thus, these models are not suitable enough for analyzing dynamic and run-time features of the organizations. This paper aims to solve this situation by proposing a model-driven platform for EA modeling, simulation, and analysis. The proposal includes the means to build executable EA models, define experiments over the models, run the experiments, observe their run-time behavior, and calculate indicator-based results enhance the decision-making process.